Bioinformatics Analysis of miRNAs and mRNAs Network-Xuefu Zhuyu Decoction Exerts Neuroprotection of Traumatic Brain Injury Mice in the Subacute Phase - Yang, Zhao-yu; Wu, Yao; Li, Xuexuan; Tang, Tao; Wang, Yang; Huang, Ze-bing; Fan, Rong (Frontiers in Pharmacology, 2022)
Xuefu Zhuyu decoction (XFZYD) is used to treat traumatic brain injury (TBI). XFZYD-based therapies have achieved good clinical outcomes in TBI. However, the underlying mechanisms of XFZYD in TBI remedy remains unclear. The study aimed to identify critical miRNAs and putative mechanisms associated with XFYZD through comprehensive bioinformatics analysis. We established a controlled cortical impact (CCI) mice model and treated the mice with XFZYD. The high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) confirmed the quality of XFZYD. The modified neurological severity score (mNSS) and Morris water maze (MWM) tests indicated that XFZYD improved the neurological deficit (P < 0.05) and cognitive function (P < 0.01). Histological analyses validated the establishment of the CCI model and the treatment effect of XFZYD. HE staining displayed that the pathological degree in the XFZYD-treated group was prominently reduced. The transcriptomic data was generated using microRNA sequencing (miRNA-seq) of the hippocampus. According to cluster analysis, the TBI group clustered together was distinct from the XFZYD group. Sixteen differentially expressed (5 upregulated; 11 downregulated) miRNAs were detected between TBI and XFZYD. The reliability of the sequencing data was confirmed by qRT-PCR. Three miRNAs (mmu-miR-142a-5p, mmu-miR-183-5p, mmu-miR-96-5p) were differentially expressed in the XFZYD compared with the TBI and consisted of the sequencing results. Bioinformatics analysis suggested that the MAPK signaling pathway contributes to TBI pathophysiology and XFZYD treatment. The present research provides an adequate bioinformatics basis for further understanding the pathogenesis and prognosis of TBI and supplies deep insights into the therapeutic effects of XFZYD.